2013
DOI: 10.1111/liv.12122
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐dihydroxyvitamin D3 and its nuclear receptor repress human α1(I) collagen expression and type I collagen formation

Abstract: Background Vitamin D deficiency is common in chronic liver disease particularly in those with severe liver fibrosis. Aims: To determine the effect of 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) on the human α1(I) collagen promoter and collagen formation by human stellate LX-2 cells and the mechanism of the effect of the vitamin D receptor (VDR) on the promoter. Methods Type I collagen was assessed by measurements of collagen mRNA and collagen protein and by transfection experiments. Binding of VDR to the α1(I) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 34 publications
5
41
0
Order By: Relevance
“…After activation, HSCs transform from quiescent vitamin A-storing cells to myofibroblast-like cells and accumulate ECM proteins, mostly type 1 collagen. Interestingly, there is in vitro evidence that VD administration may inhibit HSC activation by different pro-fibrogenic pathways (26,32). The recent findings that phototherapy improves liver histology (33) and that VD supplementation prevents liver fibrosis (26) in animal models of NAFLD support a potential role of VD in the prevention and treatment of NASH.…”
Section: Discussionmentioning
confidence: 98%
“…After activation, HSCs transform from quiescent vitamin A-storing cells to myofibroblast-like cells and accumulate ECM proteins, mostly type 1 collagen. Interestingly, there is in vitro evidence that VD administration may inhibit HSC activation by different pro-fibrogenic pathways (26,32). The recent findings that phototherapy improves liver histology (33) and that VD supplementation prevents liver fibrosis (26) in animal models of NAFLD support a potential role of VD in the prevention and treatment of NASH.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, 1,25(OH) 2 D 3 could inhibit the expression of CD40 [36]. Also, VDR overexpression vector could reduce the activities of the collagen promoter in transfected cells [37]. Previous study had illustrated that evaluation of fibroblast VDR has revealed three general classes of molecular defects, and one was decreased or absent 1,25(OH) 2 D 3 binding [38].…”
Section: Discussionmentioning
confidence: 99%
“…There is ample mechanistic understanding of the antifibrotic actions of vitamin D, including the following: (1) suppression of the renin-angiotensin and nuclear factor κB systems, 8,37,38 (2) increased expression of hepatocyte growth factor, 39 (3) direct repression of collagen I expression, 40 and (4) interference with transforming growth factor-betapromoted activation of fibrogenic genes by direct dislodging by activated vitamin D receptor complexes of SMAD3 binding to its DNA-binding elements. 41,42 We postulate that the clear decrease in fibrosis elicited by 2AMD and 2MD will lead to frank improvement in renal function with extended therapy.…”
Section: Discussionmentioning
confidence: 99%